2006
DOI: 10.1111/j.1572-0241.2006.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's Esophagus at a Tertiary Care Center: Association of Age on Incidence and Prevalence of Dysplasia and Adenocarcinoma

Abstract: Our study supports emerging data that approximately 25% of BE patients are less than 50 yr of age. While older patients had a higher prevalence of dysplasia or adenocarcinoma, the incidence of dysplasia and adenocarcinoma is similar in both age groups. Future screening strategies for BE should recognize these important findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…Finally, there is no data to support the use of transoral of symptoms, who are over the age of 50, male, and Caucasian. Th e diffi culty in risk stratifi cation is highlighted by the fact that 25 % of patients with Barrett ' s are women or under the age of 50 ( 177,178 ). Despite the well-identifi ed epidemiologic risk factors there is no clear profi le that mandates screening.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Finally, there is no data to support the use of transoral of symptoms, who are over the age of 50, male, and Caucasian. Th e diffi culty in risk stratifi cation is highlighted by the fact that 25 % of patients with Barrett ' s are women or under the age of 50 ( 177,178 ). Despite the well-identifi ed epidemiologic risk factors there is no clear profi le that mandates screening.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…The limitations of this study include the retrospective nature of the analysis and the fact that the patient population comprises mostly of older men who are at increased risk of EE [16] and BE [17] . Therefore, these data might not be applicable to populations who have higher preponderance of women and relatively younger patients.…”
Section: Resultsmentioning
confidence: 99%
“…In his study, A total of 492 cases of BE were identified in 21, 899 first endoscopies, then the prevalence and age, gender distribution of BE was successfully described, and the very similar demographics of intestinal metaplasia and intestinal metaplasia plus BE was found, which suggested they may be two consecutive stages in the same metaplastic process (van Blankenstein et al, 2005). Success of van Blankenstein and several other studies (Guardino et al, 2006;Jung et al, 2011) demonstrated the effectiveness and efficiency of primary endoscopy patients but not the large-scale population in assessing the prevalence and distribution of esophagus diseases.…”
Section: Introductionmentioning
confidence: 91%